Work commitment and motivation : A case study of a service company with a diverse workforce - Duong, Trang (fi=Turun yliopisto|en=University of Turku|, 2017)
This research aimed to explore how to improve employee work commitment through enhancing their motivation in a diverse workforce. In order to meet that research objective, this research followed three sub-objectives which helped guide the research toward suggestions of possible solutions: 1. To understand the factors affecting employees’ commitment at the workplace; 2. To identify what motivating methods could be applied by the employing organization to improve employees’ work commitment; 3. To highlight how to take diversity into account when motivating employees and enhancing their commitment to the organization. The theoretical background of the research consists of literature relating to employee work commitment and motivation. The empirical research was conducted employing a cross-sectional mixed-methods case study. The research was taken place at a big cleaning service company in Turku, Finland with more than 200 employees with diverse backgrounds. The empirical data was collected via a short questionnaire to all the employees (response rate 58.3%) and then 12 in-depth semi-structured interviews with the participants selected based on questionnaire responses. Employee commitment was divided into components based on membership and on-the-job behavior consequences together with affective, normative and continuance mindsets. The commitment profiles of these components provided a holistic view of the employees’ commitment degrees, an understanding of various antecedents, and a possibility to evaluate and influence employees’ behaviors at work. The interrelationship between commitment and motivation shows that motivating methods could be implemented by employing organization to increase work commitment. Thus, employee work commitment could be enhanced by utilizing mostly non-monetary incentives as motivators. However, they are effective only when hygiene factors are fulfilled to prevent dissatisfactions. Among various background characteristics of the workforce, length of service and culture are two factors that management need to take the diversity into consideration. In other words, some patterns of changes in commitment and behaviors over the time and the influences of cultural norms on individual perception were noticed.